Epithelial inflammation resulting from an inherited loss-of-function mutation in EGFR - Campbell, Patrick (2014)
Epidermal growth factor receptor (EGFR) signaling is fundamentally important for tissue homeostasis through EGFR/ligand interactions that stimulate numerous signal transduction pathways. Aberrant EGFR signaling has been reported in inflammatory and malignant diseases but thus far no primary inherited defects in EGFR have been recorded. Using whole-exome sequencing, we identified a homozygous loss-of-function missense mutation in EGFR (c.1283G>A; p.Gly428Asp) in a male infant with life-long inflammation affecting the skin, bowel and lungs. During the first year of life, his skin showed erosions, dry scale, and alopecia. Subsequently, there were numerous papules and pustules – similar to the rash seen in patients receiving EGFR inhibitor drugs. Skin biopsy demonstrated an altered cellular distribution of EGFR in the epidermis with reduced cell membrane labeling, and in vitro analysis of the mutant receptor revealed abrogated EGFR phosphorylation and EGF-stimulated downstream signaling. Microarray analysis on the patient’s skin highlighted disturbed differentiation/premature terminal differentiation of keratinocytes and upregulation of several inflammatory/innate immune response networks. The boy died aged 2.5 years from extensive skin and chest infections as well as electrolyte imbalance. This case highlights the major mechanism of epithelial dysfunction following EGFR signaling ablation and illustrates the broader impact of EGFR inhibition on other tissues.